Pressure-induced superconductivity and modification of Fermi surface in type-II Weyl semimetal NbIrTe4 - Qing-Ge Mu (Nature Portfolio, 2021)
Abstract Weyl semimetals (WSMs) hosting Weyl points (WPs) with different chiralities attract great interest as an object to study chirality-related physical properties, topological phase transitions, and topological superconductivity. Quantum oscillation measurements and theoretical calculations imply that the type-II WPs in NbIrTe4 are robust against the shift of chemical potential making it a good material for pressure studies on topological properties. Here we report the results of electrical transport property measurements and Raman spectroscopy studies under pressures up to 65.5 GPa accompanied by theoretical electronic structure calculations. Hall resistivity data reveal an electronic transition indicated by a change of the charge carrier from multiband character to hole-type at ~12 GPa, in agreement with the calculated Fermi surface. An onset of superconducting transition is observed at pressures above 39 GPa, with critical temperature increasing as pressure increases. Moreover, theoretical calculations indicate that WPs persist up to highly reduced unit cell volume (−17%), manifesting that NbIrTe4 is a candidate of topological superconductor.